Replacement of Memories via Reconstruction of Historical Buildings - Kırbaş Akyürek, Berrak (ICONARCH International Congress of Architecture and Planning, 2017)
Wars are the most devastating events in the world, and always end up with the destructions of the cities, deaths of several people and demolitions of the buildings. Even a war is completely over, its traumatic traces on people lives stay behind, and an intensive mourning spreads all over the towns like an infectious disease. At this point, along with two choices; replacement with new or replacement with old, architecture may have ability to rehabilitate society by compensating those destroyed in the wars. In both cases architects and city planners try to heal the mourning with canalizing the love of the loss into a new one. This study focuses on the recollective approach; the decision of replacement with old by bringing back to the copies of the demolished buildings into the future with the re-construction of their replicas. This paper aims to discuss nostalgic attempts in architecture and it's the ability to replace loss memories with the re-constructions of by-gone architecture. In this framework, several examples are analyzed and discussed into two categories; ‘immediate’ and ‘ambitious' reconstructions. Consequently, this study emphasizes that after destruction (death) of a building, memory leaves behind in its place. As mourning captures architecture, through nostalgic approaches the building and so its belonging memories are replaced with their copies.